Prognostic value of DLGAP5 in colorectal cancer - Branchi, Vittorio; García, Sebastián A.; Radhakrishnan, Praveen; Gyorffy, Balazs; Hissa, Barbara; Schneider, Martin; Reißfelder, Christoph; Schölch, Sebastian (International journal of colorectal disease, 2019)
PurposeDLG7 (disc large homolog 7) is a microtubule-associated protein encoded by DLGAP5 (DLG associated protein 5) gene and has an important role during spindle assembly. Spindle assembly deregulation is a well-known cause of genomic instability. The aim of this study was to investigate the influence of DLGAP5 expression on survival and to evaluate its potential use as a biomarker in colorectal cancer (CRC).MethodsDLGAP5 expression was measured in the primary tumor and corresponding normal mucosa samples from 109 patients with CRC and correlated to clinical and pathological data. The results were validated in a second, publically available patient cohort. Molecular effects of DLG7/DLGAP5 in CRC were analyzed via functional assays in knockdown cell lines.ResultsDLGAP5 downregulation led to a significant reduction of the invasion and migration potential in CRC. In addition, DLGAP5 expression correlates with nodal status and advanced UICC stage (III-IV).Subgroup analyses revealed a correlation between DLGAP5 overexpression and poor survival in patients with non-metastatic disease (M0). Furthermore, overexpression of DLGAP5 is associated with worse overall survival in distinct molecular CRC subtypes.ConclusionsThe results of this study suggest the importance of DLGAP5 in defining a more aggressive CRC phenotype. DLG7/DLGAP5 represents a potential biomarker for CRC in molecular subgroups of CRC.
Gesehen am 22.01.2020